Long-term prognostic factors of coronary artery disease patients after out-of-hospital cardiac arrest. (14th October 2021) - Nitta, G; Matsuda, J; Lee, T; Kato, S; Hada, Y; Inaba, O; Matsumura, Y; Nozato, T; Ashikaga, T; Sasano, T
Abstract: Background: The long-term prognosis of survival in patients with out-of-hospital cardiac arrest (OHCA) with coronary artery disease (CAD) remains poor. Methods: There were 2391 out-of-hospital cardiac arrest (OHCA) patients transferred to 2 hospitals. We included 405 cardiovascular arrest patients, who got return of spontaneous circulation (ROSC) from January 2015 to December 2018. Among them, 204 patients had CAD that caused OHCA (39%: multi-vessel disease, 19%: chronic total occlusion (CTO), 13%: vasospastic angina (VSA)). To predict mortality, we investigated patients' characteristics, pre-hospital information and findings of CAG. Results: At 1-year later, 104 patients (51%) survived. Younger age (P<0.001), VF survivor (P<0.001), pre-hospital ROSC (P<0.001), bystander CPR (P=0.013), without ECMO (P<0.001), lower lactate level on admission (P<0.001), and higher geriatric nutritional risk index score (P<0.001) were associated with low 1-year mortality, while with ST-segment elevation (P=0.778), BMI level (P=0.344), and sex (0.401) were not. And in the findings of CAG, the past history of CAD (P=0.049), the higher number of coronary vessel disease (P=0.003) such as multi-vessel disease (P=0.022), higher SYNAX score (P=0.016), and larger infarct size (max CK level; P=0.013, max CK-MB level; P<0.001) were associated with high 1-year mortality. On the other hand, acute coronary syndrome (P=0.300), any coronary lesion (RCA (P=0.447), LAD (P=0.089), LCX (P=0.096), or LMT (P=0.842)), and with CTO lesion (P=0.140) were not associated. Zero-vessel disease (VSA, P=0.001) had lower mortality among the CAD patients. In the multivariate Cox proportional hazards model, age (hazards ratio; HR: 1.03, 95%confidence interval (CI) 1.00–1.06, P<0.001) and bystander CPR (HR: 0.36, 95% CI 0.20–0.65, P<0.001) were the independent predictors of mortality. Conclusions: Younger age and pre-hospital support after OHCA with CAD were the predictors of low mortality. Pre-hospital information, systemic condition on arrival, or anatomical coronary complexity were important to predict low mortality. FUNDunding Acknowledgement: Type of funding sources: None.